Transient deoxyhemoglobin formation as a contrast for perfusion MRI studies in patients with brain tumors: a feasibility study - Stumpo, Vittorio; Sayin, Ece Su; Bellomo, Jacopo; Sobczyk, Olivia; van Niftrik, Christiaan Hendrik Bas; Sebök, Martina; Weller, Michael; Regli, Luca; Kulcsár, Zsolt; Pangalu, Athina; Bink, Andrea; Duffin, James; et al. (Frontiers in Physiology, 2024)
Interest: JF and DM contributed to the development of the automated end-tidal targeting device, RespirAct™ (Thornhill Research Inc., TRI) used in this study and have equity in the company. ESS, OS and JD are part time employees of TRI. TRI did not commission, provide support for the study, or review the manuscript. MW has received research grants from Quercis and Versameb, and honoraria for lectures or advisory board participation or consulting from Bayer, Curevac, Medac, Novartis, Novocure, Orbus, Philogen, Roche and Sandoz. All other authors have no disclosures to report.